Evaluation of Lettuce Growth, Yield, and Economic Viability Grown Vertically on Unutilized Building Wall in Dhaka City - Islam, Rinita; Solaiman, Abul Hasnat M.; Kabir, Md. Humayun; Arefin, S. M. Anamul; Azad, Md. Obyedul Kalam; Siddiqee, Mahbubul H.; Alsanius, Beatrix W.; Naznin, Most Tahera (Frontiers in Sustainable Cities, 2021)
Production of safe food in the densely populated areas of the developing countries is the most challenging issue due to the speedy urbanization, fragile food transportation facilities, and reduced farmlands. Given this background, a study was conducted to evaluate the agronomic properties and economic viability of lettuce grown vertically in the wall of building in Dhaka city, Bangladesh. Two lettuce cultivars (V1: Green wave and V2: New red fire) and three organic growing media (P1: 40% soil + 40% vermicompost + 20% coir; P2: 50% soil + 50% vermicompost; P3: 20% soil + 40% vermicompost + 40% spent mushroom compost) along with control (P0:100% soil) were used. The results revealed that plant height, leaf area, fresh weight, dry weight, and total yield of leaf lettuce were significantly increased when the green-leafed cultivar (VI) was grown in the P1 compared to all other treatments, but V2 got maximum sensory attribute scores when grown in the P1. Lettuce leaves grown in the formulated growing media (P1, P2, and P3) had higher microbial infestation whereas, a lower content occurred in the P0. The higher economic return was observed in V1P1. These results provided baseline information for further study on urban commercial vertical farming on the building walls. These demonstrate the agronomic and economic potential for vertical farming in densely populated areas but emphasize the need for optimized food safety strategies.